The Substitute Teaching Survival Guide, Grades 6-12 : Emergency Lesson Plans and Essential Advice - Dellinger, John (San Francisco Jossey-Bass, 2005)
Presents suggestions and advice for substitute teachers along with emergency lesson plans for language arts, mathematics, science, and social studies.
Keywords: Substitute teachers -- Classroom management -- Lesson planning